2020
DOI: 10.46557/001c.13745
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the Oil Price – Stock Market Nexus: Evidence From Net Oil-Importing Countries

Abstract: This study focuses on the relation between stock price returns and oil price returns covering the COVID-19 period. This relation is examined for major net oil-importing Asian countries. Utilizing daily data, we fit a DCC-GARCH model. We find evidence of a positive co-movement between oil price returns and stock price returns during the COVID-19 period. This indicates that falling oil prices act as a negative signal for the stock market.Other recent studies related to COVID-19 and its impact on various economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(144 citation statements)
references
References 33 publications
6
136
1
1
Order By: Relevance
“…Our aggregated default probability (or composite) index for Indonesian banks captures a higher potential systemic risk before the COVID-19 global pandemic. This finding adds to a growing literature showing an increase in uncertainty across global markets following the COVID-19 outbreak (see, for example, Devpura and Narayan, 2020;Haroon and Rizvi, 2020;Iyke, 2020a,b;Mishra et al, 2020;Phan and Narayan, 2020;Prabheesh et al, 2020;Salisu and and Akanni, 2020;Vidya and Prabheesh, 2020). Furthermore, we also find that the state-owned banks that own more than 50% of the total asset in the Indonesian banking industry are highly volatile around the financial crisis between June 2007 to December 2008.…”
Section: Introductionsupporting
confidence: 57%
“…Our aggregated default probability (or composite) index for Indonesian banks captures a higher potential systemic risk before the COVID-19 global pandemic. This finding adds to a growing literature showing an increase in uncertainty across global markets following the COVID-19 outbreak (see, for example, Devpura and Narayan, 2020;Haroon and Rizvi, 2020;Iyke, 2020a,b;Mishra et al, 2020;Phan and Narayan, 2020;Prabheesh et al, 2020;Salisu and and Akanni, 2020;Vidya and Prabheesh, 2020). Furthermore, we also find that the state-owned banks that own more than 50% of the total asset in the Indonesian banking industry are highly volatile around the financial crisis between June 2007 to December 2008.…”
Section: Introductionsupporting
confidence: 57%
“…Furthermore, the results suggest that the OIL_PRICE has a significant effect on all the stock indices but suggest no indication of herding behavior because the coefficient on OIL_PRICE is positive. Several previous studies have shown the significance of OIL_PRICE in international stock markets (see Narayan and Sharma, 2011;Huang and Zhang, 2020;Prabheesh et al 2020;Liu et al 2020). Changes in oil prices influence firms' current and future cash flows and subsequently affect stock returns on the international market (Jones and Kaul, 1996;Park and Ratti, 2008).…”
Section: B1 the Impact Of Global Factors On Herding Behavior In The mentioning
confidence: 97%
“…As a last point about future research, we believe the current coronavirus (COVID-19) pandemic will have significant effects on predictability of exchange rates; see recent studies by Phan and Narayan (2020) and Iyke (2020) on how COVID-19 has impacted exchange rates. In addition, there is now an evolving literature showing that COVID-19 is influencing factors that are responsible for exchange rate predictability like, for instance, oil prices and to some extent stock returns (Haroon and Rizvi, 2020;Devpura and Narayan, 2020;Prabheesh et al 2020;Gil-Alana and Monge, 2020;Narayan, 2020;Liu et al 2020;Qin et al 2020;Huang and Zheng, 2020;and Iyke, 2020b;He, Sun, Zhang and Li 2020;He, Niu, Sun, and Li, 2020). Based on evidence reported in these studies, we predict that COVID-19 will also have an impact on the evolution of Indonesia's exchange rate.…”
Section: Discussionmentioning
confidence: 85%